Mixed Finite Element Technologies - Wriggers, Peter; Carstensen, Carsten (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2009)
Mixed finite element methods are a tool to solve complex engineering problems of different nature. This subject is treated in the volume from the engineering and the mathematical point. Different applications are considered which depict the value of mixed formulations in engineering on one side. On the other side the mathematical background is provided including proofs of convergence and stability of these methods and adequate solvers for mixed problems are discussed. This broad spectrum yields an indepth treatment of mixed methods from different perspectives.